Digital Islamic Education Learning in Secondary Schools: Educational Quality and Student Engagement - Abu, Ardillah; Alhabsyi , Firdiansyah; Ruslin, Ruslin; Syam, Hijrah; Arman, Muhammad; Suktomansyah, Andi Muh.; Mudaimin, Mudaimin (LP. Ma'arif Janggan Magetan, 2025)
The integration of technology into Islamic Education (PAI) in secondary schools encounters challenges such as limited facilities and low digital competence. This study analyzes implementation strategies, supporting and inhibiting factors, and the impact of digital-based PAI learning on student quality in Central Sulawesi. A descriptive qualitative approach was used with data collected through participatory observation, in-depth interviews, and document analysis. Informants included three principals, three PAI teachers, and three students from three schools. Data analysis involved reduction, visualization with N-Vivo software, and validation with informants. The findings show that strategies include principals’ roles in policymaking and supervision, the use of educational videos, the Canva application, and the TPACK (Technological Pedagogical Content Knowledge) model. Supporting factors are leadership support, teacher readiness, and student enthusiasm. Key obstacles are limited technological devices, low teacher digital literacy, and restricted internet access. Digital-based PAI learning improves students’ digital skills, enhances learning outcomes, and strengthens critical thinking. The study concludes that with appropriate strategies and adequate resources, digital-based PAI learning can enhance student competencies. It recommends providing digital literacy training for teachers, ensuring adequate technological infrastructure, and reinforcing digital learning concepts to optimize Islamic Education in secondary schools.